Understanding the Stagnation: Attitude as a Predictor of Extensive Reading Skills without Observable Improvement Despite Metacognitive Integration - Murtadho , Nurul; Ismail, Zawawi bin; ., Kholisin (Journal of Ecohumanism, 2024)
This study explores the impact of integrating Extensive Reading (ER) enriched with metacognitive strategies on ER skills and positive attitudes towards ER learning. The research employs a one-group pretest-posttest design involving 79 Arabic language students. The measurement of ER skills and positive attitudes towards ER activities was conducted using a questionnaire based on the ten principles of ER. Bayesian paired t-tests did not show a significant improvement in skills or attitudes towards ER activities post-intervention. However, Bayesian linear regression revealed a significant correlation between post-intervention skills and attitudes, with attitudes explaining most of the variation in skills. Although no direct improvement was observed, fostering a positive attitude towards ER may indirectly enhance reading proficiency. These findings underscore the necessity of addressing both cognitive and affective aspects in Arabic language teaching.